Um olhar sobre o cotidiano e as re-definições espaciais no Bairro Potengi, Natal/RN - Machado, Fabiana Menezes (2013)
This work aims to conduct an analysis on the production of space and the dynamics between social agents that act and interact, albeit in different ways, in the production and re-production space in the Neighborhood Potengi in Natal, Rio Grande do Norte. The neighborhood is undergoing a process of dynamism undeniable and has a daily marked by heterogeneity, especially as a neighborhood in transition. So your analysis, from the perspective of the dialectical method, contributes to the understanding of the production space can be analyzed through the study of the forms and content, and may contribute to its real apprehension. After all, the city reflects forms, assumes functions, features and content that dynamic influences and is influenced by human relationships. Thus, this research seeks to analyze the production of space, based on the observation and study of the rich daily life of different social agents that operate within concrete quoted